Psychiatric Morbidities among Attenders of an Islamic Spiritual Healing Centre in Malaysia - Abdullah, Khadijah Hasanah Abang; Saini, Suriati Mohamed; Sharip, Shalisah; Shaharom, Mohamed Hatta (IIUM Medical Journal Malaysia, 2017)
Introduction: Traditional medicine which includes Islamic faith healing centre is still an important place to seek treatment whether for psychiatric reasons or others. This study aims to determine the prevalence of psychiatric illness among attenders of an Islamic spiritual healing centre and to understand patients’ illness attribution and their religiosity. Methods: A cross-sectional study was done with a systematic random sampling to obtain the prevalence of psychiatric illness which was diagnosed using Malay version of Mini International Neuropsychiatric Interview (M.I.N.I). Religiosity was measured using Hatta Islamic Religiosity Scale 1996 (HIRS96) and illness perception using Brief Illness Perception Questionnaire (BIPQ). Results: The prevalence of psychiatric illness among the attenders was 53.5%. Depressive disorder were more prevalent (41.5%) followed by anxiety disorder (28.3%), bipolar disorder (16.8%) and psychotic disorders (5.9%). More than half (58.8%) of attenders attributed their illness to supernatural causes but there were no significant difference between those with psychiatric illness and those without in terms of their attribution to supernatural causes, p=0.197.Generally, the patients had a higher religiosity score. Conclusion : This high prevalence shows a need for collaboration with the spiritual healing practitioners to improve delivery of treatment to patient and this would be a more holistic approach.